Business Plan : Ida Bakery (Frozen Food) / Aida Nazifa Rosli - Rosli, Aida Nazifa (2020)
I am Aida Nazifa Binti Rosli. My identification card number is 990206025058. I expected grade in diploma business studies. My skills are easy to engage with the public to promote my business and I also emphasize timely working hours so that my work can be completed quickly. I used my work experience at the flower shop as a motivation to run this business. From there, it helped me a lot. I run a frozen food business called the Ida Bakery. This business is located at 530, Kampung Banggol Kiat, 08200, Sik Kedah. Customers can contact me in four ways through email (aidanazifarosli@gmail.com), Facebook (Aida nazifa) and via phone number or Whatsapp. Our business offers food manufacturing and delivery food to the customers. I would like to take this opportunity to thank my lecturer, Sir Najmie Bin Osman for his support and guide to complete my assignment. Then also my friend, parents and my classmate for their support and encouragement. I really appreciated.